Integrated Quality Analysis Method of Aluminum for Composite Propellant Production - Sitompul, H. R.; Wibowo, H. B.; Abdillah, L. H.; Ardianingsih, R.; Restasari, A.; Budi, R. S.; Hartaya, K.; Baiquni, M. (Indonesian Journal of Aerospace, 2021)
Quality analysis of Aluminum powder for solid fuel composite propellant was carried out to determine the critical parameters of the composite propellant characteristics. Two types of aluminum were analyzed for quality, including bulk density and true density using the Archimedes principle, particle shape, and size using SEM (Scanning Electron Microscope), crystallinity, and purity using XRD (Xray Diffraction), particle area with BET (Brunnauer-Emmet-Teller) and BJHÂ (Barret-Joyner-Halenda) adsorption isotherm. To test the composite propellant made with 87.5% solid content and 18% AL content, then tested the characteristics of the propellant.Â The results of the analysis of the quality of aluminum for composite propellant raw materials have a very large influence on the quality of the resulting propellant, so an integrated, quick, and efficient quality analysis is needed. The critical parameters of Aluminum quality as propellant fuel are density, purity, particle shape and size, porosity/surface area, and crystallinity. Fast and efficient integrated analysis can be performed using new instruments, such as shape and size analysis with SEM, purity and crystallinity analysis with XRD, density analysis with a densitometer. AL2 which have smaller particle size, better density and shape parameters value, less pores and surface area than AL1, can be used to produce a higher quality composite propellant.